A jurisprudência trabalhista e sua importância ao jurisdicionado - Bim, Eduardo Araújo (2012)
The contemporary society craves a renowned justice, qualitative and which well serve as a guiding tool, capable of pointing the direction that the courts are waving in relation to each law. This study aims to see that this important social claim is achieved through case law in its different forms. In the specific context of the Labour Process, the research pointed out that the case-law itself does not represent an adequately way of making society feel comfortable enough about the rights they seek for. It is essential, however, to surround the court decisions by making it robust and, therefore, we have developed studies about the surrounded case-law by guiding principles, translated from its origin as well as sources and principles of legal certainty, the perfect juridical act and res judicata. We also tried to elaborate an analysis on the context of the case-law as a fundamental guarantee of the individuals who both seek to bring findings about the ways of Power between the Union s Advisory Bodies, especially the judiciary judicial branch from which emanates the decisions, those ones that are capable of bringing social peace to a particular historical and cultural context for a plaintiff firm in a democratic state of law